A Tale of Necessity and Constraints—Implementing a Community-Led Nature-Based Solution for Lake Restoration in Nepal - Devkota, Nischal; Mali, Manoj; Chhetri, Samikshya; Manandhar, Shreeya; Shrestha, Bibek; Rai, Anu; Bijlmakers, Jitse (Springer Nature, 2026)
Urban and sub-urban lakes in Nepal are facing problems associated with rapid urbanization including catchment land-use change, pollution, sediment run-off, and resource overexploitation, which are further aggravated by climate change effects. Even in these relatively developed areas, socio-economically marginalized groups are often the most affected. Hence, restoration projects must be holistic, inclusive, and evidence-based, aligning with the Nature-based Solution (NbS) framework. With these considerations, we launched a pilot project inspired by NbS called ‘Wetlands for Nepal’ at Nagdaha, a suburban lake in the Lalitpur district of Nepal, in February 2022. Our goal was to establish an evidence-based sediment and nutrient retention pond, actively guided and participated in by the community, to combat lake shrinkage and pollution from the southwest catchment. We structured the project in four phases: (i) identifying challenges and “boundary conditions” that could limit implementation; (ii) sensitizing local stakeholders and promoting collective participation; (iii) scientifically analysing catchment run-off issues; and (iv) designing and constructing an evidence-based retention pond. Run-off volume of water, catchment and lake sediment types, and total nitrogen, phosphorus and carbon of the inlet and the lake were measured in the pre-monsoon and monsoon. The results indicated that sediment loading was the major problem compared to nutrient loading in the southwest catchment; hence, the pond’s design was adapted to maximize sediment retention. We highlight the importance and potential of community-led wetland management in semi-urban and urban areas, noting relevant challenges for small to mid-scale NbS implementation in Nepal.
Keywords: Climate change adaptation; Lake restoration; Nature-based solution; Participatory wetland management; Retention pond; Taverne; Oceanography; Aquatic Science; Environmental Science (miscellaneous); Water Science and Technology; Earth and Planetary Sciences (miscellaneous); SDG 11 - Sustainable Cities and Communities; SDG 13 - Climate Action; SDG 15 - Life on Land